Geoeconomic and entrepreneurship during the COVID-19 pandemic - Maksimović, Marijana; Cvetićanin, Neven (Sociološki pregled, 2021)
The aim of this research is to examine how the coronavirus, which has become a global process, has affected the labour market. The goal is to confirm or reject the hypothesis that there has been an increase in unemployment since the beginning of the pandemic. Also, the aim is to answer the research question whether social dialogue has managed to mitigate the negative effects of the coronavirus (COVID-19). Analytical and descriptive methods were used in this research. The scientific research presented in this paper makes a significant contribution to the study of the impact of the coronavirus on the regions, economic activity and unemployment. The paper presents data on the number of the (un)employed in the world before the beginning of the pandemic and after the end of the first and most critical year.
Keywords: geographical regions; small and medium-sized enterprises; declining employment; coronavirus; social dialogue